Knowledge mapping of immunotherapy in castration-resistant prostate cancer: a bibliometric and visualized study (2003–2022) - Cai, Xianfu; Ding, Chenguang; Li, Yang; Zheng, Jin; Xue, Wujun (Frontiers in Urology, 2023)
Objective To utilize bibliometric analysis to examine the literature about immunotherapy for castration-resistant prostate cancer published within the past two decades. Through this method, we aim to visualize and analyze the research progress in this field and identify the most recent trends and developments. Methods This research conducted a comprehensive literature review on immunotherapy for castration-resistant prostate cancer. The time frame spanned from January 2003 to December 2022, and the data were extracted from the Web of Science Core Collection database. The application of various software tools, such as CiteSpace, Bibliometrix, and VOSviewer, facilitated the visualization and analysis of the gathered data. These technological utilities illustrated the progression of prominent focus areas within the field. Results After excluding irrelevant studies, 373 papers were selected for this study. The findings suggested that the field of immunotherapy for castration-resistant prostate cancer was rapidly developing. The USA was considered to have a significant early entrant advantage in this area and profoundly influenced the field. Similarly, China’s National Cancer center demonstrated notable advantages as a recent participant in this research domain. Major research institutions contributing to the field include the University of California, San Francisco; the University of Washington; and the Memorial Sloan Kettering Cancer Research Center. Notably, US authors James L. Gulley, Charles G. Drake, and Lawrence Fong had the largest number of publications in this area. The main research trends for immunotherapy of castration-resistant prostate cancer are membrane antigen expression, checkpoints T-lymphocyte-associated protein 4 (CTLA4) blockade, radium-223, and vaccines, and the refinement of establishing organoid models might fuel castration-resistant prostate cancer immunotherapy research in the ongoing development. Conclusion The key trends in immunotherapy research for castration-resistant prostate cancer are membrane antigen expression, CTLA4 blockade, radium-223, and vaccines. Exploring new immune pathways and combining different therapeutic approaches to enhance immune response will be a major trend in the field in the future.